Fractional calculus and itÂ´s applications to the non-homogeneous gauss' equations - Nishimoto, K. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
Some other many papers on fractional calculus have been reported by the author. In this paper, where firstly, we will show a table of fractional differintegrations of elementary functions which is obtained obeying the definition of author. Next we will show an application of our fractional calculus to the non-homogeneous Gauss' equation which is a differential equation of Fuchs type.